2019
DOI: 10.1109/access.2019.2925803
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Weight Estimation via Ultrasound Using Machine Learning

Abstract: Accurate fetal weight estimation is important for both fetuses and their mothers. The low birth weight (LBW, birth weight < 2500 g) and high birth weight (HBW, birth weight ≥ 4000 g) fetuses and their mothers are linked to both short and long-term health outcomes such as high perinatal mortality rate, various complications, and chronic disease in life. Because of the imbalanced small data sets and body size heterogeneities between different fetal weight groups, it is difficult for the commonly used regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Multiple performance metrics were used to evaluate the results obtained from each algorithm. For example, the weight estimation MAE and MAPE were used 17 , 18 , 49 . Similarly, for LBW classification, several performance metrics such as accuracy, precision, recall, F-score, and confusion matrix were considered 4 .…”
Section: Proposed Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple performance metrics were used to evaluate the results obtained from each algorithm. For example, the weight estimation MAE and MAPE were used 17 , 18 , 49 . Similarly, for LBW classification, several performance metrics such as accuracy, precision, recall, F-score, and confusion matrix were considered 4 .…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Most previous studies that investigate infant BW estimation and LBW classification employ ML algorithms. Feng et al 17 proposed an SVM-based classification model built using a dynamic Bayesian network (DBN) for fetal weight estimation from ultrasound parameters. The authors used a dataset collected from 7875 women with a singleton fetus in West China Secondary Hospital.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, they found that Abdominal Circumference (AC) and Estimated Fetal Weight (EFW) in week 36 or later are primary predictors of the newborn's BMI. Similarly, Feng et al [46] presented a model for EFW based on SVM and Deep Belief Network (DBN) models. The number of pregnant women who have participated in the study is 7875, including High Birth Weight (HBW) and Low Birth Weight (LBW) fetuses.…”
Section: Fetal Healthmentioning
confidence: 99%
“…It could severely hinder the classifier's ability to recognise the weed-infested regions. In order to address the issue, we implement and compare two different sampling techniques to increase the frequency of weed plant samples as for most imbalanced data sets, the application of sampling techniques does indeed aid in improved classifier accuracy [63]. Firstly, a combination of random oversampling (resample certain data points from the minority class) and undersampling (drops data points from the majority class) is used while training the model, thus increasing the ratio of weed tile samples in the dataset.…”
Section: A: Feature Vector Based Classificationmentioning
confidence: 99%